2010
DOI: 10.1007/s10725-010-9466-9
|View full text |Cite
|
Sign up to set email alerts
|

Exogenous Ca2+ alleviates nitrogen and water deficit, and improves growth of wheat (Triticum aestivum) seedlings exposed to high temperature

Abstract: This study was designed to examine whether exogenous Ca 2? would improve nitrogen nutrition, water status and growth of high temperature (HT)-stressed wheat (Triticum aestivum) seedlings. Wheat plants were exposed to 35/30 and 25/20°C as temperature control. Some of HT-stressed plants were simultaneously treated with 4 mM Ca 2? . External Ca 2? could obviously improve growth of HT-exposed wheat seedlings indicated by the biomass. Compared with Ca 2? -untreated plants, total nitrogen content showed a significan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 33 publications
0
1
0
Order By: Relevance
“…The increase in SS and Pro is likely related to Ca 2+ enhancing the activity of starch metabolism enzymes such as α and β-amylases [40], as well as the activity of P-5-CR and γ-glutamyl kinase in the Pro biosynthetic pathway [55]. External calcium could alleviate cell membrane leakage [56] and osmotic stress, induce osmotic adjustment, and maintain plant growth under stress [57]. Research showed that Ca 2+ stabilizes the cell membrane surface, affects the pH of cells, and keeps solutes from leaking out of the cytoplasm [55].…”
Section: Discussionmentioning
confidence: 99%
“…The increase in SS and Pro is likely related to Ca 2+ enhancing the activity of starch metabolism enzymes such as α and β-amylases [40], as well as the activity of P-5-CR and γ-glutamyl kinase in the Pro biosynthetic pathway [55]. External calcium could alleviate cell membrane leakage [56] and osmotic stress, induce osmotic adjustment, and maintain plant growth under stress [57]. Research showed that Ca 2+ stabilizes the cell membrane surface, affects the pH of cells, and keeps solutes from leaking out of the cytoplasm [55].…”
Section: Discussionmentioning
confidence: 99%